The Delphi technique in radiography education research. Issue 1 (September 2017) - John-Matthews, J.St.; Wallace, M.J.; Robinson, L.
Abstract: Objectives: To describe and review the Delphi technique as a tool for radiographers engaged in mixed-methods research whereby agreement is required on the proficiencies needed by educational programmes for pre- and post- registration radiographers. This is achieved through a description offering a brief history of the technique. Through a literature search, radiography education research using this technique is identified. A protocol for a research project using the technique is presented. Using this worked example, advantages and disadvantages of the method are explored including sampling of participants, sample size, number of rounds and methods of feedback. Key findings: There are limited examples of the use of the Delphi technique in radiography literature including considerations on how to select experts and panel size. Conclusion: The Delphi technique is a suitable method for establishing collective agreement in the design of radiography educational interventions. Additional research is needed to deepen this evidence-based knowledge. Highlights: The Delphi Technique is used to gain collective agreement in forecasting healthcare education priorities. There is increase of the use of the technique in healthcare education literature. There are some examples of the technique in radiography education research. A worked example of this technique is provided to critically evaluate this tool.